The social charter as a counterpart to the single European market? - Dirk Meyer (Intereconomics, 1990)
The debate over the completion of the single European market is increasingly centering on its so-called social dimension. Does it make sense to streamline social security in the member states as a safety net against the adverse consequences of the single market?
Keywords: 330; European Community